Structural characterization of polysaccharide purified from Amanita caesarea and its pharmacological basis for application in Alzheimer's disease: endoplasmic reticulum stress. Issue 21 (18th October 2021) - Hu, Wenji; Li, Zhiping; Wang, Wenqi; Song, Minkai; Dong, Ruitao; Zhou, Yulin; Li, Yu; Wang, Di
Abstract : The structural characterization and the anti-AD activities via regulation on oxidative stress-mediated endoplasmic reticulum stress of the polysaccharide purified from Amanita caesarea . Abstract : Alzheimer's disease (AD) leads to progressive declines in memory and learning. This disease may arise from endoplasmic reticulum stress due to protein misfolding, which promotes inflammatory pathway activation and induces neuronal cell apoptosis. Polysaccharide is one of the main active components of the mushroom Amanita caesarea ( A. caesarea ) and has been proven to act as an antioxidant, immune regulatory and anti-inflammatory agent with neurodevelopmental effects. In this study, polysaccharide isolated from A. caesarea (ACPS2) was subjected to analysis to determine the main components, homogeneity and molecular weight and characterize the structure. Furthermore, APP/PS1 mice were orally treated with ACPS2 for 6 weeks. Structural characterization of ACPS2 revealed a mass average molar mass of 16.6 kDa and a structure containing a main chain and branching. In vivo, treatment with ACPS2 for 6 weeks significantly improved cognition and anxious behavior in APP/PS1 mice using Morris water maze and open-field test. Alleviation of brain injury, amyloid-β deposition and tau hyperphosphorylation were observed in ACPS2-treated AD mice. No changes in other tissues were observed. ACPS2 appeared to alleviate inflammation in vivo, as determined by decreases in the serum concentrations of tumor necrosis factor-α and interleukin-1β relative to those in non-treated mice. ACPS2 improved cholinergic system function and stabilized oxidative stress in APP/PS1 mice. Proteomics and bioinformatics analyses showed that the therapeutic effect of ACPS2 is achieved through regulation of oxidative stress-mediated endoplasmic reticulum stress. Furthermore, ACPS2 exerted anti-AD effects by regulating nuclear factor-E2-related factor 2 (Nrf2) signaling, thereby inhibiting endoplasmic reticulum stress and nuclear factor-kappa B (NF-κB) activation.